Psychosocial Needs of Type-2 Diabetes Mellitus Patients in Semarang City - yanto, arief (Health Notions, 2017)
Introduction: Diabetes mellitus is a chronic disease that is difficult to cure. This causes people with diabetes mellitus have psychological pressure. The psychological needs of people with diabetes mellitus have been supported the recovery progress and the therapy program. This research aimed to know about psychosocial needs of patients with type 2 diabetes mellitus. Method: The research is descriptive quantitative with a cross-sectional approach to explore the psychosocial needs of type 2 diabetes mellitus patients. The number of samples is 96 patients with type 2 diabetes mellitus at Regional Hospital KRMT Wongsonegoro Semarang. Results: The research showed that the psychosocial needs of patients with type 2 diabetes mellitus had an average value of 33,50 with 87.5% of patients have had psychosocial needs met, and 12.5% have not adequately met. Discussion: The patients with type 2 diabetes mellitus have been at risk for psychosocial problems. The patients who are unable to meet their psychosocial needs should be taken seriously from family and service providers. Conclusion: The nurses as service providers in hospitals should be able to identify emerging problems and work to help overcome the problem of psychosocial needs experienced by patients